EFFECTS OF CARBON DIOXIDE, DICLOFENAC, AND THEIR COMBINATION ON THE COURSE OF MONOIODOACETIC ACID-INDUCED OSTEOARTHRITIS IN RATS - Shtroblia, V.V.; Lutsenko, R.V. (World of Medicine and Biology, 2025)
Osteoarthritis is the most prevalent degenerative-inflammatory joint disease. Despite the widespread use of non-steroidal anti-inflammatory drugs and physiotherapeutic approaches, the majority of patients fail to achieve sustained clinical improvement, underscoring the need for novel therapeutic strategies. In this study, osteoarthritis was induced in 60 adult male outbred white rats by a single intra-articular injection of 0.05 ml of a 3 % monoiodoacetic acid solution into the right knee joint. Animals in the control group received physiological saline, whereas experimental groups were treated with: sodium diclofenac administered intraperitoneally 1 hour prior to induction and subsequently every 3 days; carbon dioxide administered subcutaneously in the periarticular region at a dose of 0.5 ml with the same frequency; or their combination. Histological examination of the joints was performed on days 14 and 28. Administration of CO₂ and diclofenac on day 14 of therapy reduced the severity of inflammatory-destructive changes in the articular cartilage and subchondral bone. The most pronounced anti-inflammatory and chondroprotective effect was observed in the group receiving combined CO₂ and diclofenac therapy. By day 28, necrotic-degenerative changes were attenuated, accompanied by partial restoration of the morphological structure of the articular cartilage and subchondral bone. Thus, combined administration of CO₂ and diclofenac demonstrated superior efficacy compared with monotherapy with either agent alone.